Effects of omega-3 polyunsaturated fatty acids on cellular development in human ovarian granulosa tumor cells (KGN) - Yao, Yilin; Tian, Shen; Li, Ningxin; Yang, Yanzhou; Zhang, Cheng (Frontiers in Nutrition, 2022)
Emerging research has shown that polyunsaturated fatty acids (PUFAs) have positive effect on human health and exert anti-cancer effects. However, little is known about the specific mechanisms by which PUFAs regulates human ovarian granulosa tumor cells. In this study, we investigate the effects and the possible mechanisms of PUFAs on human ovarian tumor cells development. KGN cells were treated with omega-3. Small interfering (siRNA) and specific activator were used to knock down and overexpress gene expression in KGN cells. The protein content levels were analyzed by western blot. Cell viability, proliferation and apoptosis assay were performed to examine the cells development. Ane the level of glucose uptake in KGN cells were assessed by 2-DG measurement. The results showed that omega-3 treatment reduced cell viability, proliferation and increased cell apoptosis. Meanwhile, omega-3 also decreased the GLUT1/4 protein content and reduced the level of glucose uptake in KGN cells. And these changes were accompanied by the down-regulation of OCT4 expression by OCT4 siRNA. Furthermore, O4I2 (OCT4 activator) increased GLUT1/4 content and cellular glucose uptake accompanied by increased cellular viability and proliferation. Furthermore, O4I2 decreased the cell apoptosis. Our data demonstrate that omega-3 inhibits cellular development by down-regulating GLUT1/4 expression and glucose uptake in KGN cells, which are mediated through OCT4.